Unexpected discovery of a thyroid hydatid cyst during pathological examination: a case report - Imane Boujguenna; Imane Azzam; Fatima Boukis; Amine En-Nouali (Journal of Medical Case Reports)
Abstract Background Hydatid disease, a parasitic infection caused by the larval form of Echinococcus granulosus, infrequently involves the thyroid gland, whether through direct invasion or hematogenous spread. Case presentation We report the case of a 62-year-old female patient from Morocco who presented with an anterior cervical mass, initially suspected to be a goiter. A histopathological evaluation of the thyroidectomy specimen identified the presence of a hydatid cyst. A comprehensive review of the literature is also included. Conclusion Given that Morocco is an endemic region for hydatid disease, clinicians should consider this parasitic infection in the differential diagnosis of thyroid cystic lesions, recognizing the clinical and laboratory indicators of the disease.